City of Vienna, 1548 - Münster, Sebastian:::Creator:::::::::::: (Switzerland; Basel; Sebastian Heinrich-Petri, 2020)
Woodcut engraving with a simple panoramic view of Vienna from across the Danube, with labels of major buildings.